(untitled) (Journal of NELTA, 2021)
English, a means of global communication for international diplomacy, trade, work, media, and academics, has been inclusively recognized as Global Englishes (GE). This paper reviews the wider spread of English throughout the world from GE perspective and examines its impacts on the teaching of English. Moreover, it argues for the significance of GE informed pedagogy, which incorporates codeswitching, polylanguaging or translanguaging, with due respect to the diversity of English in Nepal’s context. By reviewing and analyzing related literature, it reports that GE perspective, as a paradigm that also includes World Englishes, English as Lingua Franca, English as an International Language and translanguaging, provides a new perspective for teaching English against the monolingual ‘Standard English Model’ pedagogy. Researchers have developed the teaching strategies incorporating the major themes of GE and reported positive as well as negative attitudes of the stakeholders in various contexts. This article has research and pedagogic implications as it provides useful insights for teachers and researchers for further research in this area.